Arithmetic geometry : computation and applications : 16th International Conference, Arithmetic, Geometry, Cryptography, and Coding Theory, June 19-23, 2017, Centre International de Rencontres Mathématiques, Marseille, France - International Conference "Arithmetic, Geometry, Cryptography and Coding Theory"; Aubry, Yves; Howe, Everett W.; Ritzenthaler, Christophe (Contemporary mathematics, 2019)
For thirty years, the biennial international conference AGC$^2$T (Arithmetic, Geometry, Cryptography, and Coding Theory) has brought researchers to Marseille to build connections between arithmetic geometry and its applications, originally highlighting coding theory but more recently including cryptography and other areas as well.This volume contains the proceedings of the 16th international conference, held from June 19-23, 2017.The papers are original research articles covering a large range of topics, including weight enumerators for codes, function field analogs of the Brauer-Siegel theorem, the computation of cohomological invariants of curves, the trace distributions of algebraic groups, and applications of the computation of zeta functions of curves. Despite the varied topics, the papers share a common thread: the beautiful interplay between abstract theory and explicit results.